A Raman/fluorescence dual-modal imaging guided synergistic photothermal and photodynamic therapy nanoplatform for precision cancer theranostics. Issue 41 (3rd October 2022) - Fu, Lili; Huang, Yan; Hou, Junjun; Sun, Mingzhao; Wang, Lingxiao; Wang, Xiaoyan; Chen, Lingxin
Abstract : A nanoplatform that integrates hypoxia-responsive fluorescent probe function as well as imaging and therapeutic functions is developed. Abstract : Nanoparticle-based phototherapies, such as photodynamic therapy (PDT) and photothermal therapy (PTT) are effective methods for tumor theranostics. However, there are still some problems such as lack of specificity to the special internal environment and difficulty in tumor localization. In this study, we design a near-infrared (NIR) fluorescent guided tumor therapy nanoplatform Cy-C-S-NPs for tumor therapy and precise localization. First, we synthesized a near-infrared fluorescent dye Cy-DM, combined with excellent optical and PDT/PTT properties. Interestingly, it binds Cy7 to the azo bond and mercaptoacetic acid and in the meanwhile the azo bond can be broken specifically under the condition of tumor hypoxia. Then the Au–S bond is covalently coupled with C-S-NPs, a gold nanomaterial similar to waxberry with surface-enhanced Raman function, to form the Cy-C-S-NP nanomaterial and achieve Raman imaging. In a non-anoxic environment, Cy-DM fluorescence is quenched by C-S-NPs. The unique hypoxic microenvironment of tumor cells leads to the breaking of azo bonds, releasing Cy-DM and producing fluorescence. Accurate tumor localization based on near infrared imaging diagnosis and dependent on the release of Cy-DM and C-S-NPs, PDT/PTT therapy can be performed effectively. This study provides an interesting nanoplatform that combines the functions of PDT/PTT with dual imaging effects of fluorescence and Raman imaging. This multifunctional nanoplatform may be a promising nanoplatform for targeted tumor imaging and precision therapy.